Mobile applications and its impact on the Muslim family in the view of Islamic Jurisprudence - Khattab, Amna Mahmoud Shit (International Journal of Psychosocial Rehabilitation, 2020)
Praise be to God, may God bless him and grant him peace, and humiliate everything with destiny and fate, May God bless him and grant him peace. Technical development has prevailed in all aspects of life, so I feel it in all our daily movements, in addition to the fact that technologies have become available to everyone through those applications that are specially designed for mobile phones, and some of them are known to be useful, such as applications for public information or religious information.